Pengenalan Prinsip Kaizen Dan Penanganan Barang Berbahaya (Dangerous Goods) pada PT. Kereta Api Logistik (KALOG) di Jakarta Pada Tahun 2020 - Lis Lesmini; Wynd Rizaldy; Irwan Chaerudin (Jurnal Abdimas Transportasi & Logistik, 2022)
PT. Railway Logistics (KALOG) as a partner in this PKM is a company engaged in the field of rail-based freight transportation with business fields in the form of logistics distribution, container terminal management, loading and unloading, warehousing, packing, labeling, transportation, tracking, logistics escort and logistics management. The problem of partner priority is the lack of human resources who understand specifically about the application of Kaizen principles and the handling of dangerous goods, especially for the delivery of goods by train. The purpose of this activity is; Provide basic knowledge of kaizen principles, handling dangerous goods and the formation of a profitability mindset for employees. The event was held on Thursday, March 12, 2020 at the Office of PT. KALOG, Railway Warehousing Complex, Kp Bandan Rt. 2/4, Jakarta 14430. Methods of Activities with training, Q&A and video playback. The stages of the activity are: a. Stage of Proposal Making, b. Survey Stage: Review of the location of devotion to PT. KALOG and conducted an interview with the Chairman of PT. Local KALOG, c. The stage of identification of partner problems and identification of equipment needs for socialization, d. Stages of Implementation of activities and the final stage, namely the creation of reports and articles of PKM journals. The result of this activity is the increasing knowledge and understanding of participants about the importance of applying the principles of Kaizen and Dangerous Goods in creating profitability and safety and security of freight by train. Participants of the activity are 26 people consisting of leaders, employees and stake holders from PT. KALOG numbered plus 4 Lecturers and 5 ITL students The survey results showed that socialization was effective because it was able to increase the knowledge and understanding of participants in the principles of Kaizen and Dangerous Goods in handling goods, especially by train